2004
DOI: 10.1021/jf030663a
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Volatile Components and Their Odor Characteristics of Green and Ripe Fruits and Dried Pericarp of Japanese Pepper (Xanthoxylum piperitum DC.)

Abstract: The essential oils of green and ripe fruits and dried pericarp of Japanese pepper (Xanthoxylum piperitum DC.), which are commonly used in Japanese dishes as spices, were extracted with methanol, followed by adsorption to Porapak Q resin. Their aroma profiles were characterized by a sensory evaluation, and their chemical constituents were investigated by using gas chromatography (GC), gas chromatography-mass spectrometry, and aroma extract dilution analysis. Geraniol, citronellal, linalool, and methyl cinnamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 22 publications
4
43
0
1
Order By: Relevance
“…In mature leaflets (0.5-2.5 cm), the diameter of secretory cavities was 122.6±17.3 µm and there were 24.5±3.1 secretory cavities per leaflet ( Figure 1F). It has been previously reported that monoterpene hydrocarbons such as D-limonene, β-phellandrene, and β-myrcene are major components of Japanese pepper immature fruits and sesquiterpenes are present as minor components (Jiang and Kubota 2004;Sekiwa-Iijima et al 2002). Here, we examined the levels of volatile terpenoids in the different tissues of Japanese pepper.…”
Section: Morphological Characterization Of Secretory Cavities and Quamentioning
confidence: 96%
See 1 more Smart Citation
“…In mature leaflets (0.5-2.5 cm), the diameter of secretory cavities was 122.6±17.3 µm and there were 24.5±3.1 secretory cavities per leaflet ( Figure 1F). It has been previously reported that monoterpene hydrocarbons such as D-limonene, β-phellandrene, and β-myrcene are major components of Japanese pepper immature fruits and sesquiterpenes are present as minor components (Jiang and Kubota 2004;Sekiwa-Iijima et al 2002). Here, we examined the levels of volatile terpenoids in the different tissues of Japanese pepper.…”
Section: Morphological Characterization Of Secretory Cavities and Quamentioning
confidence: 96%
“…For plants native to Asia, little is known regarding the biosynthetic genes associated with terpene formation in Japanese pepper, despite a survey of specialized metabolite analysis in the genus Zanthoxylum (Jiang and Kubota 2001;Jiang and Kubota 2004;Sekiwa-Iijima et al 2002). Here, we investigated terpene formation in different developmental stages of Japanese pepper leaves, and performed a detailed morphological analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The flavor components also change during maturation of the fruits. 4) It can also be assumed that the pungency and distribution of the pungent components vary with the part of the Japanese pepper and the maturation stage of the fruits. Although -, -, and -sanshools, the all-trans isomer of -sanshool referred to here as -sanshool, and hydroxy -and -sanshools have been identified as the pungent substances in many varieties of Japanese pepper, [5][6][7][8][9][10][11] not much is known about their distribution in various parts of the plant, at different stages of development of the fruits, or in Japanese pepper grown in various locations.…”
mentioning
confidence: 99%
“…초피에서 분리 동정된 화합물로는 초피잎에서 protocatechuic acid [12], 향기관련 물질로 과피 정유로부터 geranyl acetate, citronellol, alpha-terpineol, citronellal, linalool 과 isopulegol [15][16][17], polymeric procyanidin [20], aliphatic acid amide [8], hydroxyl-alpha-sanshool [19], quercetin과 kaempferol [7], 그리고 2종류의 세레토인 유도체인 N,N-dimethylserotonin 5-O-β-glucoside (1a)와 N-methylser- Retension index on a HP-5MS column. Retension index on a HP-5MS column.…”
unclassified